A systematic review of the nexus between climate change and social media: present status, trends, and future challenges - Sultana, Bebe Chand; Prodhan, Md. Tabiur Rahman; Alam, Edris; Sohel, Md. Salman; Bari, A. B. M. Mainul; Pal, Subodh Chandra; Islam, Md. Kamrul; Islam, Abu Reza Md. Towfiqul (Frontiers in Communication, 2024)
Social media and climate change are some of the most controversial issues of the 21st century. Despite numerous studies, our understanding of current social media trends, popular hot topics, and future challenges related to climate change remains significantly limited. This research presents a systematic review of climate change and social media for the first time. Review the studies published between 2009 and 2022 in places like Google Scholar, Science Direct, Web-of-Science, Scopus, ResearchGate, and others. For this systematic review, we found 1057 articles. Forty-five articles were the most relevant according to our goals and study design, which followed the PRISMA framework. The results of this review demonstrate that Twitter is the most popular platform. Every year, we identify rising trends in the number of publications. Past studies often focused on just one social media site, like Twitter (n = 26) or Facebook (n = 5). Although most studies focus on the United States, the study area is primarily "all over the world." This study offers a theoretical framework by examining the relationship between social media platforms and the discourse surrounding climate change. It looked into how social media trends influence public perception, raise awareness, and spur action on climate change. In practical terms, the study focuses on important and trending topics like nonbelievers and climate change. The contribution consists of synthesizing the body of research, providing insights into the state of the digital world, and suggesting future lines of inquiry for the field of social media and climate change studies. We highlighted the studies' quality assessment result of "moderate quality." This systematic review provides information about how climate change is now portrayed on social media and lays the groundwork for further study in this area